First experimental measurements of 2D microdosimetry maps in proton therapy. Issue 1 (19th September 2022) - Guardiola, Consuelo; Bachiller‐Perea, Diana; Kole, Emmanuel M. Mate; Fleta, Celeste; Quirion, David; De Marzi, Ludovic; Gómez, Faustino
Abstract: Background: Empirical data in proton therapy indicate that relative biological effectiveness (RBE) is not constant, and it is directly related to the linear energy transfer (LET). The experimental assessment of LET with high resolution would be a powerful tool for minimizing the LET hot spots in intensity‐modulated proton therapy, RBE‐ or LET‐guided evaluation and optimization to achieve biologically optimized proton plans, verifying the theoretical predictions of variable proton RBE models, and so on. This could impact clinical outcomes by reducing toxicities in organs at risk. Purpose: The present work shows the first 2D LET maps obtained at a proton therapy facility using the double scattering delivery mode in clinical conditions by means of new silicon 3D‐cylindrical microdetectors. Methods: The device consists of a matrix of 121 independent silicon‐based detectors that have 3D‐cylindrical electrodes of 25‐µm diameter and 20‐µm depth, resulting each one of them in a well‐defined micrometric radiation sensitive volume etched inside the silicon. They have been specifically designed for a hadron therapy, improving the performance of current silicon‐based microdosimeters. Microdosimetry spectra were obtained at different positions of the Bragg curve by using a water‐equivalent phantom along an 89‐MeV pristine proton beam generated in the Y1 proton passive scattering beamline of the Orsay Proton Therapy Centre (Institut Curie, France). Results: Microdosimetry 2D‐maps showing the variation of the lineal energy with depth in the three dimensions were obtained in situ during irradiation at clinical fluence rates (∼10 8  s −1  cm −2 ) for the first time with a spatial resolution of 200 µm, the highest achieved in the transverse plane so far. The experimental results were cross‐checked with Monte Carlo simulations and a good agreement between the spectra shapes was found. The experimental frequency‐mean lineal energy values in silicon were 1.858 ± 0.019 keV µm −1 at the entrance, 2.61 ± 0.03 keV µm −1 at the proximal distance, 4.97 ± 0.05 keV µm −1 close to the Bragg peak, and 8.6 ± 0.1 keV µm −1 at the distal edge. They are in good agreement with the expected trends in the literature in clinical proton beams. Conclusions: We present the first 2D microdosimetry maps obtained in situ during irradiation at clinical fluence rates in proton therapy. Our results show that the arrays of 3D‐cylindrical microdetectors are a reliable microdosimeter to evaluate LET maps not only in the longitudinal axis of the beam, but also in the transverse plane allowing for LET characterization in three dimensions. This work is a proof of principle showing the capacity of our system to deliver LET 2D maps. This kind of experimental data is needed to validate variable proton RBE models and to optimize LET‐guided plans.